A case study on the soil–pile–structure interaction of a long span arched structure. Issue 12 (1st December 2016) - Kildashti, Kamyar; M. Dolatshahi, Kiarash; Mirghaderi, Rasoul
Abstract: Different concepts for modelling of soil-foundation in complete dynamic interaction analysis for a 110-m height 70-m span arched structure on 180 piles were investigated in this paper. The modelling approaches consisted of a sophisticated procedure to account for soil compliance and foundation flexibility by defining frequency-dependent springs and dashpots; namely, flexible-impedance base model. The results of this model were compared with those of the conventional modelling procedures; namely, fixed base model and flexible base model by defining frequency-independent springs. In the flexible-impedance base model, the substructure approach was employed through finite element modelling. To account for the kinematic interaction, the numerical model of the soil, foundation and piles were developed using a verified finite element model in ABAQUS. The free field time history and design spectrum were modified to obtain the foundation input motion. The impedance of pile groups with different length was obtained by the finite element model to assess the inertial interaction. The comparison of the results of the employed models showed that rocking and torsional responses were greatly affected by soil–structure interaction, indicating redistribution of seismic demands. It was also proven that the internal demands of the conventional model considering frequency-independent Winkler springs might be higher than those of the model including pile–soil–structure interaction effects.